HUBUNGAN PERSEPSI PERAWAT PELAKSANA TENTANG GAYA KEPEMIMPINAN KEPALA RUANGAN DENGAN KINERJA PERAWAT PELAKSANA DALAM MELAKSANAKAN TINDAKAN KEPERAWATAN - ROHAYANI, LILIS (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2013)
Leadership style of head nurse is a group of characteristics used by leader to influence nurse  on duty in ferforming nursing care, so it would need evaluation over their echietment at work to earn best result.. Thisresearch aims to known the picture and relationship between leadership style and the work of nurse. Research design used is cross sectional. Population to this research are 54 nurse on duty come from SPK dan D3 of nursing. Sample to the research werw collected from 53 nurse on duty which was using total sampling technique. Data collecting was done by questionaire. Dta analysisi was through two steps, those are univariante to see frecuency distribution and bivariant to see the relationship (chi Squre). Statistical test result shows P value=0,087 meaning at alpha 0,05 it can be concluded there is no significante difference between leadership style of head ward nurse and the work of nurse on duty. Nevertheks, at alpha 0,1 shows significant differentbetween leadership style of head ward nurse and the work of nurse on duty from ood ratio (OR) it can be conclude the authoritative leadership style has change to give better work for 2, 091 (0,119-36,64) timescompared to liberal leadership style, democratic leadership style has change to gyve better work for 0,545 (0,029-10,37) times compad to the liberal /laissez faire. It is suggested to head ward nurse to modify theirleadership style in approprrate with situation dan condition/Conditional, the presence of leadership trinning or forming of cadres, and evaluation over work achievement of nurse on duty. Keyword : leadership style, work, cross sectional, total sampling technique